Dripping Technology Use Among Young Adult E-Cigarette Users. (July 2021) - Massey, Zachary B; Brockenberry, Laurel O; Murray, Tori E; Harrell, Paul T
Background: Young adults are increasingly using electronic nicotine delivery systems (ENDS). The standard ENDS device involves an electric coil that heats a wick to vaporize an e-liquid solution. "Dripping" is another method that involves applying e-liquid directly to the coil. Dripping increases risk of harmful toxic compounds in vapor aerosols. Despite evidence of high levels of dripping among adolescents, young adult prevalence is unknown. Methods: Young adults aged 18 to 24 completed an online survey assessing vaping and dripping status, type of devices used, tobacco use, and vaping expectancies. Among ever-vapers, univariate and multivariate logistic regression models assessed whether demographics predicted dripping and use of dripping devices. Multivariate Analysis of Variance compared never- and ever-drippers on expectancies for vaping outcomes. Results: Over 2 in 5 young adult ever-vapers (43.7%) reported dripping. A multivariate regression model found that male gender (AOR = 1.83), identifying as White (AOR = 2.37), and use of other tobacco products (hookah; AOR = 1.91; cigars; AOR = 2.26; cigarettes; AOR = 2.51) were associated with dripping. E-cigarette users who reported lifetime dripping were more likely to consider vaping stimulating, socially facilitating, and flavorful. They ascribed lower health risks to vaping and felt it could reduce negative affect, weight gain, nicotine cravings, and boredom (all P < .05). Conclusion: Dripping was a highly prevalent behavior among this sample of young adults, particularly among White males. These findings point to the importance of gaining a greater understanding of the drivers and consequences of vaping and dripping behavior.